Bedrock petrology controls on hydrogeochemistry and fluoride concentrations in Precambrian aquifers of central Benin, Western Africa. (October 2021) - Tossou, Yao Yélidji Joël; Yessoufou, Soulémana; Orban, Philippe; Vander Auwera, Jacqueline; Boukari, Moussa; Brouyère, Serge
Abstract: In central Benin, fluoride concentrations in groundwater generally exceed the national and WHO guideline values (1.5 mg/L) and are locally above 7 mg/L (max. 7.19 mg/L). In this area, aquifers are found in a Precambrian bedrock made of migmatitic gneiss and granites. Recent hydrogeochemical studies have shown that the occurrence of fluoride in groundwater in this area is of geogenic origin. The aims of this investigation are to determine the sources of fluorine in the bedrock and to assess the role of geology on the mineralization and high fluoride concentrations in groundwater. Thirty-five rock samples were collected in different areas that display contrasting concentrations of fluoride in groundwater. We carried out analyses of petrology, mineralogy and geochemistry on the samples. The results show that fluorine concentrations vary between 100 and 2900 ppm. Several fluorine-bearing minerals such as (biotite, muscovite, amphibole), titanite, fluorite, fluor-apatite, fluor-allanite, epidote and chlorite were identified. Groundwaters with elevated concentrations of fluoride are found in geological aquifers units and watershed rocks that contain fluorine bearing minerals. Biotite occurring in the granitic formations has the highest fluorine concentrations and appears as the most important contributor to the total fluorine from the bedrock to the groundwater. Highlights: In central Benin, the groundwater fluoride concentrations are geogenic. Fluorine concentrations in the bedrock range from 100 to 2900 ppm. Among the bedrock F-bearing minerals, biotite is the most important.